(untitled) (Cardiovascular Journal, 2013)
Background: Few studies have assessed the relation of Serum creatinine and serum blood urea nitrogen (BUN) level with the severity of coronary artery disease (CAD). This study investigated the association between high uric acid BUN levels with the presence of Coronary artery disease. Materials and Methods: This study was designed as an observational cohort study. The study was composed of 170 patients admitted at our institution due to symptoms related to CAD. Patients having angiographic evidence of stenosis in coronary artery were as case group and without stenosis control group. Patients with high serum creatinine were defined as serum creatinine concentration with in 80-105 ?mol/L and BUN level with in 10-20 ?mol/L. The presence of CAD has been defined as the Gensini score being >1. Results: Patients with or without CAD were similar in terms of age (45.22±6.80 years vs. 52.87±9.31 years, p<0.01) and significant age difference was found between patients. Male gender (p<0.001) and smoking habit (p=0.003) were more frequent and statistically significant in patients with CAD. There was a statistically significant difference between the mean serum creatinine levels (92.89±20.82 ?mol/L vs 108.68±23.62 ?mol/L respectively, p<0.05) and serum blood urea nitrogen level (10.59±6.15 ?mol/L vs. 20.37±6.73 ?mol/L respectively, p<0.01) of patients with or without CAD. While looking at the correlation coefficient of Gensini score with different factors; S. creatinine, ejection fraction and BUN were significantly correlated at<0.001 and <0.04 and <0.01 level respectively. Increased serum creatinine levels were found to be independent risk factors for the presence of CAD (for serum cretinine hazard ration 3.9, p<0.001 and in case BUN hazard ration 2.08, p<0.001). Conclusion: In conclusion, a significant association has been found between serum creatinine & BUN level and the presence of CAD. In addition to the evaluation of conventional risk factors in daily clinical practice, the measurement of serum creatinine and BUN level might provide significant prognostic benefits in terms of global cardiovascular risk and management of the patients. DOI: http://dx.doi.org/10.3329/cardio.v5i2.14282 Cardiovasc. j. 2013; 5(2): 141-145